Monoclonal antibodies - A new era in the treatment of multiple myeloma - Jelinek, Tomas; Hajek, Roman (Blood reviews, 2016)
Monoclonal antibodies (mAbs) are currently the most investigated therapeutic compounds in oncology, but there is no monoclonal antibody approved in the treatment of multiple myeloma (MM). Nevertheless several really promising molecules are under investigation in phase III clinical trials. Dominantly daratumumab (anti-CD38) and elotuzumab (anti-CS1) showed extraordinary effectiveness in phase I/II trials. The toxicity was acceptable which is important for their addition to standard anti-myeloma agents like proteasome inhibitors or immunomodulatory drugs. Monoclonal antibodies such as denosumab (anti-RANKL) or BHQ880 (anti-DKK-1) are investigated also in the management of myeloma bone disease. This review is focused on the most promising mAbs, their mechanisms of action and the rationale of use. Practically all available results have been described. If the ongoing trials confirm the efficacy and safety of mAbs, they would become an important part of MM treatment that would be translated in the further improvement of therapeutic outcomes.
Keywords: Lorvotuzumab; klinické zkoušky jako téma; Clinical Trials as Topic; Elotuzumab; výsledek terapie; Bone disease; nemoci kostí; BHQ880; Antibodies, Monoclonal; Multiple myeloma; cílená molekulární terapie; lidé; Daratumumab; Antineoplastic Agents; protinádorové látky; mnohočetný myelom; Treatment Outcome; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Bone Diseases; Siltuximab; Monoclonal antibodies; Denosumab; monoklonální protilátky; Multiple Myeloma; Molecular Targeted Therapy; Pembrolizumab; Humans